PENGARUH PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE TEAM ASSISTED INDIVIDUALIZATION TERHADAP PEMAHAMAN KONSEP MATEMATIS PESERTA DIDIK - Angryanof, Natasya Putri (Departemen Matematika, 2023)
Concepts understanding of mathematical is one of learning mathematics purposes that have be possessed by students. Based on the results of tests conducted at SMA Negeri 2 Payakumbuh, it was found that concepts understanding of mathematical by students' was still low. The research purpose is to find out, analyze and describe the understanding of mathematical concepts of students who study with the TAI type by model of cooperative learning and compare with students who study to use the TAI type by model of cooperative learning is better than the concepts understanding of the mathematical by students in conventional classes. This research type is a quasi-experimental research design with Static Group Design. The research population in this research was class XI MIPA 1 – XI MIPA 8 of SMA Negeri 2 Payakumbuh. It can be concluded that the TAI type by model of cooperative learning has an influence on concepts understanding of the mathematical by students. Keywords – Cooperative, TAI, Mathematical concepts understanding